The Use of Journalistic Media in Students and Lecturers of State Universities in Medan City - M Yoserizal Saragih; Ahmad Tamrin Sikumbang; Winda Kustiawan (MASI Mandiri Edukasi, 2026)
The rapid expansion of digital media has transformed journalistic media consumption patterns in higher education, raising concerns about information credibility and increasing vulnerability to misinformation. This study aims to analyse differences in patterns, preferences, and objectives of journalistic media use between university students and lecturers in Medan City. The research employed a qualitative descriptive approach, with data collected through in-depth interviews, observations, and documentation involving students and lecturers from several higher education institutions. The findings reveal clear differences between the two groups. Students tend to rely on social media platforms and digital news portals due to their speed, ease of access, and compatibility with digital lifestyles. At the same time, lecturers predominantly use more credible and analytical journalistic sources, such as Kompas.com, Tempo.co, and academic journals to support teaching and research activities. Variations influence these differences in digital literacy levels, information needs, and attitudes toward misinformation. Students are found to be more vulnerable to hoaxes, whereas lecturers demonstrate more critical and selective information practices. The study highlights the importance of strengthening media literacy in higher education through curriculum integration, targeted training, and collaboration with media professionals to foster a credible and educational digital information ecosystem.